Influence of Conductor Pipe Diameter on the Global Structural Performance of a Fixed Offshore Wellhead Platform - Afriza Akbar Ardiansyah; Luh Putri Adnyani; Jumat Amin; Rahmawati (Indonesian Journal of Maritime Technology, 2026)
Offshore wellhead platforms are continuously subjected to environmental loads from waves, currents, and wind; therefore, structural assessment is required to ensure safe operation, particularly when design modifications are proposed. This study evaluates the influence of conductor pipe diameter variation on the global structural performance of an existing fixed offshore wellhead platform by comparing the existing 20-inch conductor pipe configuration (CP20) with a modified 30-inch conductor pipe configuration (CP30). The assessment was conducted through in-place analysis using SACS software under 1-year operating and 100-year storm conditions. The structural performance was evaluated based on displacement response, member unity check, joint unity check, and pile axial capacity. The results show that both CP20 and CP30 configurations satisfy the strength requirements, with maximum member unity checks of 0.81 under operating conditions and 0.96 under storm conditions, which are below the allowable limit of 1.00. The joint unity checks also remain far below the allowable limit, with values of 0.177 under operating conditions and 0.172 under storm conditions. The pile axial capacity is also satisfactory, with pile safety factors ranging from 29.41 to 34.04 for CP20 and from 29.41 to 30.21 for CP30, which are significantly higher than the minimum requirement of 1.50. However, several displacement responses exceed the allowable limits. The pilehead displacement under storm conditions reaches 6.49 cm for CP20 and 6.51 cm for CP30, exceeding the allowable limit of 5.08 cm. The vertical deck displacement under storm conditions reaches 7.42 cm for CP20 and 7.44 cm for CP30, exceeding the allowable limit of 4.00 cm. In addition, the horizontal displacement exceeds the allowable limit of 3.10 cm under both operating and storm conditions, with values increasing from 5.9194 cm to 8.4834 cm for CP20 and from 5.9294 cm to 8.5323 cm for CP30. These findings indicate that increasing the conductor diameter from 20 inches to 30 inches has a limited effect on global strength capacity but produces a slight increase in displacement response due to the larger hydrodynamic loading area. Therefore, the CP30 modification can be considered acceptable from a strength-capacity perspective, but further evaluation of serviceability performance.